Detection of methicillin-resistant Staphylococcus aureus and multidrug resistance isolated from cats in animal clinic at Sidoarjo District, East Java, Indonesia - YUSAC KRISTANTO KHODA WARUWU; ASWIN RAFIF KHAIRULLAH; MUSTOFA HELMI EFFENDI; BAMBANG SEKTIARI LUKISWANTO; DANIAH ASHRI AFNANI; SHENDY CANADYA KURNIAWAN; OTTO SAHAT MARTUA SILAEN; KATTY HENDRIANA PRISCILIA RiwuRIWU; AGUS WIDODO; SANCAKA CHASYER RAMANDINIANTO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Waruwu YKK, Khairullah AR, Effendi MH, Lukiswanto BS, Afnani DA, Kurniawan SC, Silaen OSM, Riwu KHP, Widodo A, Ramandinianto SC. 2023. Detection of methicillin-resistant Staphylococcus aureus and multidrug resistance isolated from cats in animal clinic at Sidoarjo District, East Java, Indonesia. Biodiversitas 24: 106-111. Methicillin-resistant Staphylococcus aureus is the name given to the strain of bacteria that is multidrug-resistant (MDR) and resistant to ?-lactam antibiotics. Comparatively to other livestock, companion animals have been highlighted more often as potential MRSA reservoirs. This study looked for MDR and cat-derived MRSA strains in Sidoarjo. One hundred cats with nasal swabs were accessed, along with the veterinary hospital and other clinics. Samples were collected using a sterile cotton swab and buffered peptone water as the transport medium, and then identified using a microbiological standard operating procedure. On five different antibiotic discs, the Kirby-Bauer diffusion method was used to determine the S. aureus antibiotic resistance profile. As a confirmatory test for MRSA, S. aureus isolates that were resistant to cefoxitin continued to grow on Oxacillin Resistance Screening Agar Base (ORSAB). Out of the seven MRSA isolates that were assumed to be MRSA, four of the seven MRSA isolates were confirmed to be MDR S. aureus. Humans and companion animals can both act as reservoirs for the recirculation of MRSA strains within the same household because cat nasal swabs resemble nosocomial MRSA and because both are more likely to get colonized than infected. It illustrated how cats might be a health risk to the public and acted as a cautionary tale about the inappropriate use of antibiotics.